An Evaluative Framework for Mutual and Employee-Owned Businesses. Issue 3 (1st September 2016) - Tischer, Daniel; Yeoman, Ruth; White, Stuart; Nicholls, Alex; Michie, Jonathan
ABSTRACT: Mutual and employee-owned businesses (MEOBs) continue to experience a revival in the UK, be it through the growth of building societies and financial mutuals, or the success of employee-owned businesses. In addition, government has promoted MEOBs by transferring public services into new corporate forms, citing reports of resilience and long-term success of MEOBs. Yet despite these developments, there appears to be some ambiguity as to how to evaluate the performance of MEOBs. The lack of a coherent framework that takes the values, principles and structures into account when assessing outputs and outcomes results in a narrow understanding of MEOB performance, often focused on quantitative measures irrespective of the values and principles held by these types of organizations, and indeed their purpose. In an effort to advance such work, this paper seeks to outline a framework to evaluate mutual and employee-owned businesses taking account of a variety of dimensions that affect how MEOBs do business, and the outcomes they produce, to broaden the idea of performance by joining up values and principles that are at the centre of the mutual model with the outputs and outcomes that are being created.